Additional diagnosis, observations of breeding biology and tadpole of a little known dwarf puddle frog, Phrynobatrachus inexpectatus (Anura: Phrynobatrachidae) - Tiutenko, Arthur; Zinenko, Oleksandr (Salamandra, 2020)
Phrynobatrachus inexpectatus and P. minutus are sister species of dwarf-size puddle frogs endemic to humid montane forests in the Ethiopian highlands. For almost two decades P. inexpectatus was officially known only from two populations, although a wider distribution was assumed. We confirm a population of this species in Harenna Forest (Bale Zone), at 1,400-2,400 m a.s.l. and report observations of its ecology and breeding biology, including descriptions of its advertisement call and tadpole. Phrynobatrachus minutus was long believed to be distributed east of the Great Rift Valley in the same forested area, but we did not find any evidence of this species in the area surveyed. We discuss the misidentification of these species by previous researchers and replace P. minutus with P. inexpectatus in the amphibian species list of the Harenna Forest. An additional diagnostic description of P. inexpectatus is provided that should help to distinguish this species from P. minutus and from the sympatric members of the P. natalensis complex.
CRIS-Team WoS Importer:2020-06-05

Alai! Alai! – a new species of the Gloydius halys (Pallas, 1776) complex (Viperidae, Crotalinae), including a brief review of the complex - Wagner, Philipp; Tiutenko, Arthur; Mazepa, Glib; Borkin, Leo J.; Simonov, Evgeniy (Amphibia-Reptilia, 2016)
During a scientific field expedition to the Alai-Pamir range five specimens of the genus Gloydius have been collected in the larger Alai. A morphological and genetical examination of the specimens has shown that they are part of the G. halys complex, but represent a new taxon which is characterized by the following unique character combination: It is a slender and moderately stout small snake, up to 479 mm total length. The head has nine symmetrical plates on the upper head, 7 supralabial and 8-9 infralabial scales. Body scales in 20-22 rows around midbody, 143-156 ventral and 35-45 usually paired subcaudal scales. The cloacal plate not divided. The general coloration consists of various different tones of olive, tan and brown, having a distinct head, but an indistinct body pattern with, excluding the tail, 26-29 transverse crossbands, which are not extending to the sides of the body. The haplotype network shows the new species within the G. halys complex and close related to both, G. h. halys and G. h. caraganus. So far the new described species is only known from the Alai range. However, various Gloydius specimens are found in Kyrgyzstan and because of the complicated taxonomy those specimens have to re-identified to clarify their status and the status of the new species.<br
Keywords: Alai; Central Asia; Crotalinae; Gloydius rickmersi sp. n.; Kyrgyzstan; Viperidae

A new record of Pseudoboodon gascae Peracca, 1897 (Squamata: Serpentes: Lamprophiidae) from the southern edge of the Ethiopian Highlands - Tiutenko, Arthur (Herpetology Notes, 2018)
I here report the first record of Pseudoboodon gascae from a forest habitat in southern Harenna Forest, Bale Zone, Oromia, Ethiopia.<br
Keywords: Biogeography; snakes; Africa

A new species of African legless skink, genus Acontias Cuvier, 1816 “1817” (Squamata: Scincidae) from Serra da Neve inselberg, south-western Angola - Marques, Mariana P.; Parrinha, Diogo; Tiutenko, Arthur; Lopes-Lima, Manuel; Bauer, Aaron M.; Ceríaco, Luis M.P. (African Journal of Herpetology, 2023)
During a recent survey of the Serra da Neve inselberg in south-western Angola, a population of legless skinks of the genus Acontias was found. Only three species of this genus have been recorded for the country so far–A. occidentalis, A. kgalagadi and A. jappi. Using an integrative approach and combining molecular and morphological data we found that the Serra da Neve population represents a new species, closely related to species such as A. percivali and some members of the A. occidentalis species complex. In this paper, we describe this population as a new species, Acontias mukwandosp. nov. and provide brief comments on its conservation and biogeography.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Acontinae; endemism; speciation; systematics; taxonomy

A new species of Erythrolamprus (Serpentes: Dipsadidae: Xenodontini) from the savannas of northern South America - Entiauspe-Neto, Omar Machado; Abegg, Arthur Diesel; Koch, Claudia; Nuñez, Leroy P.; Azevedo, Weverton Dos Santos; Moraes, Leandro J.C.L.; Tiutenko, Arthur; Bialves, Tatiane S.; Loebmann, Daniel (Salamandra, 2021)
Erythrolamprus Boie, 1826 is a highly diverse dipsadid snake genus, ranging from Central America south to Argentina and Uruguay. In this work, we reassess the taxonomic status of specimens previously identified as Erythrolamprus poecilogyrus schotti (Schlegel, 1837) from the savannah habitats of Roraima state, northern Brazil, Guyana, and Bolívar state, Venezuela. Based on novel molecular and morphological evidence, we conclude that these specimens represent a distinct, diagnosable and reciprocally monophyletic taxon. We here describe it as a new pecies. Furthermore, we comment on the taxonomy of other Erythrolamprus spp..<br
CRIS-Team Scopus Importer:2021-06-11
Keywords: Brazil; Erythrolamprus sp. nov.; E. p. schotti; molecular phylogeny; morphology; open habitats; Squamata; taxonomy; Venezuela.

A new species of leptopelis (Anura, arthroleptidae) from the south-eastern slope of the ethiopian highlands, with notes on the leptopelis gramineus species complex and the revalidation of a previously synonymised species - Tiutenko, Arthur; Zinenko, Oleksandr (ZooKeys, 2021)
A new ground-dwelling species of treefrog in the genus Leptopelis is described from the Harenna Forest in south-eastern Ethiopia. The description is based on morphology and acoustics and is supported by molecular data. The new species has a small body size, and the digital discs on fingers and toes are significantly more conspicuous than in other semi-fossorial members of the L. gramineus complex. It occupies forest habitats at lower altitudes and is separated ecologically and geographically from high-altitude species of the complex. One of them, a parapatric cryptic species from Bale and Arsi Mountains, is resurrected from synonymy of L. gramineus and given a new name, L. montanus. Genetic barcoding of specimens from both populations showed that they belong to two distinct lineages that had been revealed by recent phylogenetic research. To confirm the geographic separation of the studied populations, the collection area of L. gramineus types was verified through analysis of the diary and the final report of the 2nd expedition of V. Bottego, and through matching of the route described in it with modern maps. The type locality of L. gramineus sensu stricto is restricted to Gamo Gofa, Ethiopia. Following the results of recent phylogenetic studies, the range of L. gramineus is limited to west of the Great Rift Valley. An identification key to the named Ethiopian species of the genus is provided.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Bale Mountains; Ethiopia; Harenna Forest; Leptopelis diffidens sp. nov; Leptopelis montanus nom. nov; Leptopelis rugosus; Pseudocassina ocellata; Pseudocassina rugosa

A new species of Namib Day Gecko (Gekkonidae: Rhoptropus Peters, 1869) from the Serra da Neve inselberg, southwestern Angola - Parrinha, Diogo; Marques, Mariana P.; Tiutenko, Arthur; Heinicke, Mathew P; Ceríaco, Luís Miguel Pires; Bauer, Aaron Matthew (Zootaxa, 2025)
The genus Rhoptropus comprises nine recognized species of diurnal geckos endemic to the arid regions of Angola and Namibia. Seven species occur in Angola, including the widespread R. boultoni and the poorly known Angolan endemics R. benguellensis and R. montanus, formerly recognized as subspecies of R. boultoni. While R. benguellensis is relatively widespread in the Angolan Escarpment, R. montanus is geographically restricted to the Huíla Plateau. Recent fieldwork in the Serra da Neve inselberg, a herpetological diversity hotspot in southwestern Angola, revealed the presence of a putatively undescribed species of Rhoptropus in the highlands of the inselberg. An integrative taxonomic approach combining coloration, morphological and molecular data supports the recognition of this population as a distinct taxonomic unit with affinities to R. montanus, which we describe herein as Rhoptropis nivimontanus sp. nov.The discovery of a new species of Rhoptropus endemic to Serra da Neve is discussed in the biogeographic context of the regio
Keywords: Africa; endemism; escarpment; systematics; taxonomy

An island in a sea of sand: a first checklist of the herpetofauna of the Serra da Neve inselberg, southwestern Angola - Marques, Mariana P.; Parrinha, Diogo; Lopes-Lima, Manuel; Tiutenko, Arthur; Bauer, Aaron M.; Ceríaco, Luis M.P. (ZooKeys, 2024)
The Serra da Neve inselberg in Namibe Province, southwestern Angola is the second highest peak of Angola with an elevation of 2489 m. It remains one of the least explored regions in the country, despite several endemic species having been recently described from this inselberg. Here we provide an inventory of the amphibian and reptile species occurring in Serra da Neve and compare its fauna with that of the surrounding habitats at lower elevations, as well as an examination of the phylogeographic affinities of the inselberg taxa. A total of 60 herpetological taxa were recorded for the Serra da Neve inselberg and its immediate surroundings. These include 11 species of amphibians, belonging to nine genera and seven different families, and 49 species of reptiles, belonging to 32 genera and 12 families. Of these, one amphibian and seven reptiles from seven different genera are strictly endemic, turning the inselberg into the richest region in southwestern Africa with respect to strict endemics, with a total of one endemic reptile taxa per 127 km2. Not surprisingly, most of the recorded taxa belong to clades that are endemic, or at least strongly associated, with southern Africa, but two are representatives of central African clades, and other two are more closely related to eastern African highland taxa. We also provide comments on the threats to the conservation of this endemic-rich inselberg.<br
Keywords: Amphibians; Reptiles; Inselberg; Angola; Southwestern Africa; Biodiversity; Endemism; Taxonomy; Conservation

A treasure trove of endemics: two new species of snake-eyed skinks of the genus Panaspis Cope, 1868 (Squamata: Scincidae) from the Serra da Neve Inselberg, southwestern Angola - Marques, Mariana P.; Parrinha, Diogo; Lopes-Lima, Manuel; Tiutenko, Arthur; Bauer, Aaron Matthew; Ceríaco, Luís Miguel Pires (Evolutionary Systematics, 2024)
Four species of the genus Panaspis – P. cabindae, P. wahlbergi, P. maculicollis and P. mocamedensis – are currently known from Angola. The analysis of recently collected specimens from Serra da Neve Inselberg, an isolated mountain located in northern Namibe Province, revealed unexpected taxonomic diversty in the group. Using an integrative taxonomy approach based on morphological and DNA sequence data, with both mitochondrial (16S) and nuclear (RAG-1) genes, we were able to distinguish two distinct populations, described here as two new species, Panaspis ericae sp. nov. and P. mundavambo sp. nov. Both species are assumed to be endemic to the inselberg. This reinforces our notion of southwestern Angola as a hotspot of skink diversity, and highlights the urgent need for the conservation of Serra da Neve.<br
Keywords: reptiles; integrative taxonomy; Africa; herpetofauna; cryptic species

Citizen Science meets specimens in old formalin filled jars: a new species of Banded Rubber Frog, genus Phrynomantis (Anura, Phrynomeridae) from Angola - Ceríaco, Luís Miguel Pires; Santos, Bruna S.; Pimentel Marques, Mariana; Bauer, Aaron Matthew; Tiutenko, Arthur (Alytes, 2021)
Three species of Phrynomantis Peters, 1867, have been historically recorded for Angola: P. affinis, P. annectens andP. bifasciatus. As noted by all authors who have dealt with specimens of P. bifasciatus from the country, the Angolan population is characterized by an odd coloration pattern for the species, which led Boulenger to consider it a different variety. A revision of the extant specimens of Angolan Phrynomantisavailable in natural history collections, specimens collected in recent field surveys, as well as recent sightings and photographs allows the recognition of the Angolan population of P. cf. bifasciatus as a new species, endemic to the coastal lowlands of western Angola. The new taxon is described solely based on its coloration pattern and morphology, and it is separated from nominotypic P. bifasciatus by more than one thousand kilometers. The revision of these historical specimens also allowed us to confirm a second record of P. affinis in the country and to contribute to an overall better understanding of the distribution of the species of the genus on the continent.

Coital biting in a captive montane egg-eater (Dasypeltis atra) - Tiutenko, Arthur (African Journal of Herpetology, 2023)
Coital biting, a behaviour where the male grabs and holds the female with his mouth before or during copulation, is seldom observed in snakes. It has been reported mainly in North American and some Eurasian colubrids, including the genera Coronella, Drymarchon‎, Elaphe, Farancia, Lampropeltis, Pantherophis, Pituophis, Sonora, and Zamenis (Tinkle 1951; Gillingham 1974; Lotze 1975; Lewke 1979; Secor 1987; Langford and Borden 2004; Aßmann et al. 2016, Johansen et al. 2022). A comparison of coital bite occurrences with phylogeny of snakes led Senter et al. (2014) to conclude that this behavioural phenomenon is likely to be ancestral for the group they called “Eurasian ratsnake clade Zamenis + (Elaphe + (Coronella + Lampropeltini))” in the family Colubridae. However, the authors of this first-ever study of the evolutionary history of courtship in snakes conceded that the inference that such behaviour is absent in a clade must be treated with caution because in nature such behaviours may not always be observed and may thus remain unrecorded. Also, important information about the biology and behaviour of captive reptiles often remains unknown to the scientific community because hobbyists and commercial breeders often lack contact with academic herpetologists and do not publish their observations. Even when such observations are mentioned in online publications or herpetoculture magazines, they are often overlooked by professional herpetologists. This article reports for the first time a case of coital biting in Montane Egg-eater (Dasypeltis atr
Keywords: Herpetologie; Afrika

Einsatz der Standards von IMS Global Learning Consortium bei der Erstellung der Lehrmaterialien für Sprachkurse: Einschränkungen und Lösungen - Tiutenko, Arthur (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
The following article reports on practical experience in the usage of the Question and Test Interoperability Specification of the IMS Global Learning Consortium for the production of language courses. The many problems that both the authors of learning content and software developers encounter in striving to implement the standard need to be solved with as little negative effect as possible on the quality of the learning materials. Given that it is not always possible to maintain confor- mance with a standard, it is, arguably, not the standards as such that are impor- tant, but rather the abandonment of binary data storage and the usage of open, XML-based formats.
Keywords: E-Learning

Extraordinary claims require extraordinary evidence: on the taxonomic identity of Phalotris cerradensis Silveira, 2020 - Entiauspe-Neto, Omar Machado; Tiutenko, Arthur; Azevedo, Weverton Dos Santos; Abegg, Arthur Diesel (Revue Suisse De Zoologie, 2021)
Phalotris Cope, 1862 is a fossorial dipsadid snake genus that encompasses 15 species, distributed mainly in open areas from Northeastern Brazil to Southern Argentina. Some of its species are known from small series, and there is little to no knowledge on their morphological variation and species delimitations. In this work, we analyze the taxonomic status of Phalotris cerradensis Silveira, 2020, a recently described species known from a single specimen, and provide evidence for its synonymy with Phalotris concolor Ferrarezzi, 1993.<br
CRIS-Team WoS Importer:2021-05-28
Keywords: lapomorphinim Neotropical; Synonym; Systematics

Fifteen shades of green: The evolution of Bufotes toads revisited - Dufresnes, Christophe; Mazepa, Glib; Jablonski, Daniel; Oliveira, Ricardo Caliari; Wenseleers, Tom; Shabanov, Dmytro A.; Auer, Markus; Ernst, Raffael; Koch, Claudia; Ramírez-Chaves, Héctor E.; Mulder, Kevin Patrick; Simonov, Evgeniy; et al. (Molecular Phylogenetics and Evolution, 2019)
The radiation of Palearctic green toads (Bufotes) holds great potential to evaluate the role of hybridization in phylogeography at multiple stages along the speciation continuum. With fifteen species representing three ploidy levels, this model system is particularly attractive to examine the causes and consequences of allopolyploidization, a prevalent yet enigmatic pathway towards hybrid speciation. Despite substantial efforts, the evolutionary history of this species complex remains largely blurred by the lack of consistency among the corresponding literature. To get a fresh, comprehensive view on Bufotes phylogeography, here we combined genome-wide multilocus analyses (RAD-seq) with an extensive compilation of mitochondrial, genome size, niche modelling, distribution and phenotypic (bioacoustics, morphometrics, toxin composition) datasets, representing hundreds of populations throughout Eurasia. We provide a fully resolved nuclear phylogeny for Bufotes and highlight exceptional cyto-nuclear discordances characteristic of complete mtDNA replacement (in 20% of species), mitochondrial surfing during post-glacial expansions, and the formation of homoploid hybrid populations. Moreover, we traced the origin of several allopolyploids down to species level, showing that all were exclusively fathered by the West Himalayan B. latastii but mothered by several diploid forms inhabiting Central Asian lowlands, an asymmetry consistent with hypotheses on mate choice and Dobzhansky-Muller incompatibilities. Their intermediate call phenotypes potentially allowed for rapid reproductive isolation, while toxin compositions converged towards the ecologically-closest parent. Across the radiation, we pinpoint a stepwise progression of reproductive isolation through time, with a threshold below which hybridizability is irrespective of divergence (<6My), above which species barely admix and eventually evolve different mating calls (6–10My), or can successfully cross-breed through allopolyploidization (>15My). Finally, we clarified the taxonomy of Bufotes (including genetic analyses of type series) and formally described two new species, B. cypriensis sp. nov. (endemic to Cyprus) and B. perrini sp. nov. (endemic to Central Asia). Embracing the genomic age, our framework marks the advent of a new exciting era for evolutionary research in these iconic amphibians.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Allopolyploidization; Bufonidae; Cryptic species; Green toads; Hybrid speciation; RAD sequencing

First records of a long reed frog genus Hyperolius from the eastern Ethiopian Highlands - Tiutenko, Arthur; Spawls, Timothy; Zinenko, Oleksandr (Herpetology Notes, 2023)
CRIS-Team Scopus Importer:2023-03-10

Generic affinities of African house snakes revised: a new genus for Boodon erlangeri (Serpentes: Elapoidea: Lamprophiidae: Lamprophiinae) - Tiutenko, Arthur; Koch, Claudia; Pabijan, Maciej; Zinenko, Oleksandr (Salamandra, 2022)
Lamprophis erlangeri is a lamprophiid snake endemic to moist montane forest remnants and formerly forested areas in the south and south-west of the Ethiopian highlands. Its vernacular name ‘Ethiopian House Snake’ is a result of century-long speculations about the generic placement of this species. New molecular and morphological data brought evidence that it has been misplaced in both genera of ‘African house snakes’, Lamprophis and Boaedon. A new genus is described to accommodate L. erlangeri. It represents a sister clade to the Western and Central African genera Bothrophthal-mus and Bothrolycus from which it differs by general body form and proportions, head shape, number of preocular scales, absence of loreal pits, maxillary dentition as well as by a number of cranial features. The type locality of the type species of the new genus, originally ‘Somaliland’, is restricted in this paper to Abera in Ethiopia. Lamprophis abyssinicus, the second Ethiopian endemic in this genus is assigned again to the genus Pseudoboodon on a basis of similar external morphology and cranial osteology. In the course of this revision of systematic affinities in Lamprophis and Boaedon, also the status of the genus Alopecion, considered to represent a junior synonym of these genera, is revalidated. It is reinstated as a valid monotypic genus, to include L. guttatus, a South-African species with similarly turbulent taxonomic history as of L. er-langeri. Cranial osteology of L. erlangeri, L. abyssinicus, and L. guttatus is analysed for the first time. Morphological, ecological and behavioural characters of the related genera Alopecion, Boaedon, Bothrolycus, Bothrophthalmus, Lamprophis, Lycodonomorphus, Pseudoboodon, and of the new genus are reviewed and compared.
CRIS-Team Scopus Importer:2022-11-18
Keywords: Alopecion annulifer; Boaedon abyssinicus; Boaedon erlangeri; Boaedon guttatus; Boaedontini; cranial osteology; Lamprophis abyssinicus; Lamprophis guttatus; molecular genetics; morphology; osteology; Pseudoboodon; skull; Squamata; systematics; taxonomy

Generic affinities of African house snakes revised: a new genus for Lamprophis inornatus (Serpentes: Lamprophiidae: Lamprophiinae: Boaedontini) - Tiutenko, Arthur; Maliuk, Anastasiia; Koch, Claudia (Salamandra, 2025)
This article is the second part of a revision of the systematics of Boaedontini Dowling, 1969 and a follow-up to the work by Tiutenko et al. (2022). As a result of morphological and phylogenetic analyses, further taxonomic actions are taken in the genus Lycodonomorphus Fitzinger, 1843. Lamprophis inornatus Duméril, Bibron & Duméril, 1854, a species initially described in the genus Lamprophis and subsequently assigned to Lycodonomorphus, is here transferred to a new monotypic genus on a basis of combined criteria including genetic distance, morphology, ecology and biogeography. For improved taxonomic stability of the species and the new genus, a neotype for L. inornatus is designated from the specimen ZFMK 032712. The lectotype of Boodon infernalis Günther, 1858 is designated from one of three extant syntypes NHMUK 1858.4.11.5 and the type locality of this species, that is currently treated as a junior synonym of L. inornatus, is restricted to Durban, South Africa. The name ‘infernalis’ should be available if the species status of this northern clade would become restored. Lycodonomorphus subtaeniatus Laurent, 1954, another former Lycodonomorphus species long assumed to be a member of Boaedon, is here formally assigned to this genus and tentatively placed next to Boaedon upembae (Laurent, 1954) and Boaedon virgatus (Hallowell, 1854) on a basis of pholidosis, cranial morphology and dentition. The tribe Boaedontini now contains nine genera that can be separated by morphological characters according to the proposed key. The genus Lycodonomorphus still requires attention of taxonomists, as it contains species, such as L. bicolor, L. laevissimus, L. leleupi, L. mlanjensis, L. obscuriventris, and L. whytii, with uncertain taxonomic position and in this sense has to be viewed as sensu lat
Keywords: Elaiophis; nomenclature; osteology; skull; Squamata; taxonomy

More than meets no eyes: Taxonomic status of a Liotyphlops Peters, 1881 (Serpentes: Anomalepididae) blindsnake from the Atlantic Rainforest - Entiauspe-Neto, Omar M.; Franco, Francisco L.; Koch, Claudia; Tiutenko, Arthur; Wingert, Juliana M.; Borges-Martins, Marcio (Zoologischer Anzeiger, 2023)
Liotyphlops Peters, 1881 is an anomalepidid blindsnake genus that encompasses 12 species, widely distributed in Central and South America. In this study, we evaluate the taxonomic status of Liotyphlops sousai Santos & Reis, 2018, a species described based on a single specimen from the Atlantic Rainforest of southern Brazil, and after analyzing evidences based upon molecular systematics, external morphology and osteology, we propose its synonymy with Liotyphlops beui (Amaral, 1924), a common and widely distributed Anomalepidid species. We also provide comments and recommendations on the taxonomy of Liotyphlops, assessing the risks associated with describing a new species based on small type series.
CRIS-Team WoS Importer:2023-03-10

Namen von Literatur- und Filmhelden als expressive und wertende Benennungseinheiten in Wörtebuch und Wortschatz - Tiutenko, Arthur; Prokopchuk, Klavdiya; et al. (Problemy frazeologii i leksykografii, 2000)
Keywords: Pharaseologie; Eigenname; Anspielung

New distributional records for the herpetofauna in the southern Ethiopian Highlands - Tiutenko, Arthur (Conference: 19th European Congress of Herpetology, 2017)
Keywords: Herpetologie

On the taxonomic status of apostolepis roncadori lema, 2016 and apostolepis vittata (Cope, 1887) (serpentes: Dipsdidae) Sobre el estatus taxonómico de apostolepis roncadori lema, 2016 y apostolepis vittata (Cope, 1887) (serpentes: dipsadidae) - Entiauspe-Neto, Omar Machado; Tiutenko, Arthur (Revista Latinoamericana de Herpetologia, 2020)
Apostolepis Cope, 1862 is a speciose dipsadid snake genus. Among its more than 30 taxa, several species are known only from small series of specimens. The lack of basic information about morphological variations and natural history has resulted in a difficult taxonomic history of the group. We revisit the taxonomic status of the recently described Apostolepis roncadori Lema, 2016 and argue about its synonymy with a previously long-known species Apostolepis vittata Cope, 1887, considering their diagnostic characters either do not differ or the difference can be attributed to intraspecific variation.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Elapomorphini; Neotropical; Synonym; Systematics

Prinzipien einer sprachübergreifenden Typologie von Lern-und Testaufgaben für elektronische Sprachlehrwerke - Tiutenko, Arthur; Koller, Gerhard (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
Technical solutions usually adopted for computer-based language teaching and testing materials were developed for purposes other than language learning. To understand the features offered by this technology and to formulate the requirements for their further development and improvement, the authors of language teaching materials need to know which types of learning tasks are realizable with modern technology in general. To establish a standard typology of learning and testing tasks, a system of classification categories is necessary that cannot be borrowed from any of the typologies already developed for traditional language teaching. A possible system of such criteria is discussed in the article.<br
Keywords: E-Learning

Raising of Lazarus: Rediscovery and redescription of Apostolepis niceforoi Amaral, 1935 (Serpentes: Dipsadidae: Elapomorphini) - Entiauspe-Neto, Omar M.; Medina Rangel, Guido Fabian; Guedes, Thais B.; Tiutenko, Arthur (Holotipus rivista di zoologia sistematica e tassonomia, 2020)
Apostolepis is a speciose Neotropical snake genus, encompassing 38 species, widely distributed in South America. Most species of the genus are known based on small series, which has contributed to a convoluted taxonomic history. In this study, we report the rediscovery of Apostolepis niceforoi, a taxon that remained knownfrom a single specimen since its original description in 1935, providing a detailed redescription, with c
Keywords: Caenophidia; Colombia; Neotropical; Taxonomy

Rediscovery of a rare and endangered Apostolepis (Serpentes: Dipsadidae): reassessing species boundaries and phylogenetic relationships using integrative approaches - Entiauspe-Neto, Omar M.; Giraudo, Alejandro; Guedes, Thais; Tiutenko, Arthur; Borges-Martins, Marcio; Koch, Claudia (Salamandra, 2025)
Apostolepis is a diverse genus of small and fossorial dipsadid snakes, comprising 34 species ranging from Colombia southwards into Argentina. Most species are known from small series and very little is known regarding their phylogenetic relationships, morphological variation and diagnoses, which has caused a widespread historical taxonomic instability for the genus. Its southernmost representative, Apostolepis quirogai, is known solely from three specimens from the Mesopotamian and Uruguayan Savannas, with no new records in the last two decades. Its rarity, puzzling external morphology, and unique coloration pattern have significantly contributed to an uncertain systematic relationship for this species. We report the rediscovery of A. quirogai, providing an integrative species delimitation based on multivariate analyses, external morphology and molecular systematics, a redescription, an updated account of its morphological variation, geographic distribution, and a description of its cranial osteology. We provide a new phylogenetic hypothesis for the Elapomorphini, where we consistently recover A. quirogai nested within the Apostolepis assimilis species group, which is redefined and discussed here. We also provide a comparative osteological analysis of skull morphology for Apostolepis, providing insights into diagnostic characters and cranial evolution for the grou
Keywords: Elapomorphini; integrative taxonomy; morphology; Neotropics; osteology; Squamata

Revisiting the taxonomic status of Apostolepis sanctaeritae, a forgotten Neotropical dipsadid snake - Entiauspe-Neto, Omar M.; Koch, Claudia; Guedes, Thais B.; Tiutenko, Arthur (Salamandra, 2020)
Apostolepis COPE, 1862 is a highly diversified and speciose Neotropical dipsadid genus, encompassing almost 40 species of fossorial or cryptozoic snakes, widely distributed east of the Andes. In this work, we revisit the taxonomic status of A. sanctaeritae WERNER, 1924, a rather controversial taxon described from a single specimen. Apostolepis sanctaeritae has been subject to several synonymizations and revalidations, being currently relegated as a junior synonym of Apostolepis cearensis COMES, 1915. A careful reanalysis of its coloration pattern, pholidosis, and a detailed description of the skull morphology of A. sanctaeritae, based on Cr-scan data of the holotype, provide compelling evidence for its revalidation. Furthermore, we consider A. ammodites FERRAREZZI, BARBO & ALBUQUERQUE, 2005 as a junior synonym of A. sanctaeritae, considering a total overlap of important diagnostic characters of coloration (large snout blotch reaching up to the frontals, wide black nuchal collar), pholidosis (rostral scale does not reach one/half of its interprefrontal suture), osteology (curved dentary, with 8-9 teeth loci; prearticular crest slightly higher than surangular crest), and geographic distribution (recorded from the Cerrado of Brazil). We also present a detailed osteological description and taxonomic account for A. sanctaeritae plus brief comments on the taxonomy of Apostolepis, suggesting major changes for the current framework seen in recent publications.
CRIS-Team WoS Importer:2020-11-27

Systematics of African house snakes revisited: News about systematic placement of two former Lamprophis species endemic to the Ethiopian highlands - Tiutenko, Arthur (15th Conference of the Herpetological Association of Africa, 2023)
The systematic affinities of two rare and little-known lamprophiid snakes have been reviewed. One of these species has been long known either as Lamprophis erlangeri or as Boaedon erlangeri. It is endemic to moist montane forest remnants and formerly forested areas in the south and south-west of the Ethiopian highlands. New molecular and morphological data brought evidence that this species has been misplaced in both genera of ‘African house snakes’. A new genus has been described that represents a sister clade to the Western and Central African genera Bothrophthalmus and Bothrolycus from which it differs by general body form and proportions, head shape, number of preocular scales, absence of loreal pits, maxillary dentition as well as by a number of cranial features. The second Ethiopian endemic, Lamprophis abyssinicus, that had been treated in the recent past as a close relative of Lamprophis erlangeri was assigned in the course of this revision to the genus Pseudoboodon on a basis of similar external morphology and cranial osteology.<br
Keywords: Herpetologie

SZOnline: Ein integriertes Informationssystem für Online-Sprachunterricht und automatis- ierte Sprachtests - Kamm, Roland; Tiutenko, Arthur (Fremdsprachenlernen online. Erfahrungen und Erkenntnisse im Projektverbund SprachChancen, 2007)
The language didactics places the main focus on active, systematic knowledge transfer from a teacher to a learner and on frequent exercise rather then on self-studying and gradual knowledge acquisition as in the didactics of most other (usually academic) subjects. For the quality of computer-based language teaching not only constant interaction of a learner with the teacher or the study colleagues is essential but also with the technical system that organizes, directs and as possi- ble controls the learning process. We consider a technical system for online teaching of languages as a part of a broad IT infrastructure in a language institute. A concept of such software is presented in the following article.
Keywords: E-Learning

Tadpole of Leptopelis diffidens Tiutenko & Zinenko, 2021 (Anura, Arthroleptidae) - Tiutenko, Arthur (Alytes, 2023)
The tadpole of Leptopelis diffidens is described to complete the data on this new species whose description was published a year earlier. It is compared with the tadpoles of sympatric and parapatric congeners – L. ragazzii and L. shebellensis. The description of the latter is extended and corrected. Hypotheses about breeding seasonality of L. diffidens and L. shebellensis are raised.<br

Tadpole of Leptopelis ragazzii (Boulenger, 1896), Shoa Forest Tree Frog (Anura, Arthroleptidae) - Tiutenko, Arthur; Zinenko, Oleksandr (Herpetozoa, 2019)
The tadpole of poorly studied Leptopelis ragazzii (Boulenger, 1896), a high-altitude tree frog species from the Ethiopian highlands, is described for the first time and compared with closely related sympatric species - L. gramineus (Boulenger, 1898) and L. vannutellii (Boulenger, 1898).
CRIS-Team WoS Importer:2019-07-02

Tadpole of Leptopelis ragazzii (Boulenger, 1896), Shoa Forest Tree Frog (Anura, Arthroleptidae) - Tiutenko, Arthur; Zinenko, Oleksandr (Herpetozoa, 2019)
The tadpole of poorly studied Leptopelis ragazzii (Boulenger, 1896), a high-altitude tree frog species from the Ethiopian highlands, is described for the first time and compared with closely related sympatric species - L. gramineus (Boulenger, 1898) and L. vannutellii (Boulenger, 1898).
CRIS-Team Scopus Importer:2024-12-16
Keywords: Arthroleptidae; Ethiopia; Harenna forest; Larva; Leptopelis gramineus; Leptopelis vannutellii; Tadpole

Taxonomic status of Apostolepis barrioi Lema, 1978, with comments on the taxonomic instability of Apostolepis Cope, 1862 (Serpentes, Dipsadidae) - Entiauspe-Neto, Omar Machado; De Sena, Arthur; Tiutenko, Arthur; Loebmann, Daniel (ZooKeys, 2019)
Apostolepis is a diverse neotropical snake genus, which has been historically subjected to poor taxonomic descriptions, largely based on either a small type series or subjective diagnoses. We evaluate the case of Apostolepis barrioi Lema, 1978 and its intricate taxonomic history, suggesting its synonymization with Apostolepis dimidiata (Jan, 1862), and providing brief commentary on the taxonomic instability that has been plaguing the genus.
CRIS-Team WoS Importer:2019-05-09

Taxonomic status of Apostolepis tertulianobeui Lema, 2004 based on an integrative revision of Apostolepis assimilis (Reinhardt, 1861) (Serpentes: Dipsadidae) - Entiauspe-Neto, Omar M.; Koch, Claudia; Gray, Russell J.; Tiutenko, Arthur; Loebmann, Daniel; Guedes, Thaís B. (Zoologischer Anzeiger, 2021)
Apostolepis is a diverse Dipsadid snake genus, with 35 known species, inhabiting most of South America at east of the Andes. In this study, we redescribe Apostolepis assimilis Reinhardt, 1861, and evaluate the taxonomic status of a controversial taxon, Apostolepis tertulianobeui, described based on a single specimen from an unknown locality of Minas Gerais state, southeastern Brazil. A careful reanalysis of the type specimen and additional material provides compelling evidence for the synonymy of A. tertulianobeui with A. assimilis. We also provide comments on the taxonomy of Apostolepis, osteological and hemipenial descriptions, and a species distribution modelling for A. assimilis.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Cranial morphology; Elapomorphini; Hemipenial morphology; Neotropics; Species distribution modelling; Taxonomy

Text im Hypertext. Ein textlinguistischer Blick auf die Informationsgestaltung im Internet - Prokopchuk, Klavdiya; Tiutenko, Arthur (Jahrbuch für Computerphilologie, 2001)
A look from the viewpoint of the linguistic theory of text, as in this article, may result in reconsideration of some key-ideas common to many non-linguistic publications about hypertext. Since hypertext is frequently thought of as a primarily textual phenomenon (single text or system of texts), the authors of this article search for its linguistic definition based upon the knowledge about text production and reception that was gathered by many researchers in text linguistics during past four decades. A genuine concept of hypertext developed by computer science in 1960s—1980s serves in this case as a framework for the discussion. The article shows that verbal components of hypertext have to satisfy the general textuality criteria to become texts. Those criteria, however, clash with the notion of hypertext as a kind of non-constrained text and make the philosophical vision of an unlimited, universal hypertext unrealistic.<br
Keywords: linguistics; textuality

Textparadigma und Hypertext - Prokopchuk, Klavdiya; Tiutenko, Arthur (Paradygmaty filozofii języka, literatury i teorii tekstu (pogranicza metodologiczne), 2004)
Keywords: Textlinguistik

The genus Holaspis (Squamata: Lacertidae) in Angola: a tale of forgotten specimens and disappearing forests, with the description of a new species - Parrinha, Diogo; Marques, Mariana P.; Gonçalves, Francisco M. P.; Tiutenko, Arthur; Bauer, Aaron Matthew; Ceríaco, Luis M.P. (Salamandra, 2025)
The members of the Afrotropical lacertid genus Holaspis are strikingly specialized lizards, adapted for gliding in forest canopies, with serrated blue tails. Two species are currently recognized within the genus: Holaspis guentheri from West and Central Africa, and Holaspis laevis from East Africa. The currently known southern limits of H. guentheri are in the northern Angolan Guineo-Congolian habitats, which are remnants of forests connecting the country to West/Central Africa. The oldest record of the species in Angola, dating back to the 19th century, is based on a currently lost specimen collected by José d’Anchieta near Caconda, southwest Angola. Caconda is situated on the Angolan Central Plateau, which is part of the Great Escarpment of southern Africa. The loss of Anchieta’s specimen and its geographic context led most authors to disregard it, leaving its taxonomic identity dubious until now. The rediscovery of two additional specimens from Caconda, collected by William John Ansorge in the early 20th century and deposited in the Natural History Museum, London, allowed us to confirm the presence of the genus in the region, prompting targeted surveys and examination of additional material. Our surveys failed to locate any Holaspis near Caconda, with alarming rates of deforestation in the region raising the possibility that this population may already be extinct. The reexamination of the extant Caconda specimens and comparison with H. guentheri and H. laevis revealed consistent morphological differences that suggests that the Caconda population may represent a distinct taxonomic unit. Here we describe the Holaspis from Caconda as a new species, presumably endemic to the Angolan Central Plateau. These findings and their implications are discussed in the biogeographical context of the highlands of western Angola, a recognized hotspot of diversity and endemism for several taxonomic group
Keywords: Taxonomy; biogeography; natural history collections; deforestation; highlands; Lacertidae; Holaspis

The Trachylepis (Squamata: Scincidae) of Angola: an integrative taxonomic review with the description of seven new species - Ceríaco, Luis M.P.; Marques, Mariana P.; Parrinha, Diogo; Tiutenko, Arthur; Weinell, Jeffrey I.; Butler, Brett O.; Bauer, Aaron M. (Bulletin of the American Museum of Natural History, 2024)
The genus Trachylepis is currently represented by 21 species in Angola, most of them part of nomenclaturally and taxonomically challenging species complexes. In this study we present an inte- grative taxonomic revision of the genus in Angola and describe seven new species: Trachylepis attenboroughi, sp. nov., Trachylepis bouri, sp. nov., Trachylepis hilariae, sp. nov., Trachylepis ovahelelo, sp. nov., Trachylepis suzanae, sp. nov., Trachylepis vunongue, sp. nov., and Trachylepis wilsoni, sp. nov. As result of our taxonomic revisions, 25 valid Trachylepis species are now confirmed from Angola. A phylogenetic analysis using a combination of mitochondrial (16S, ND2) and nuclear (RAG1) markers, as well as morphological data, supports the recognition of the new species. In addition, data support the revalidation of Trachylepis albopunctata (Bocage, 1867), Trachylepis notabilis (Peters, 1879), and Trachylepis ansorgii (Boulenger, 1907). We also provide a redefinition of Euprepes anchi- etae Bocage, 1866, which we synonymize with Trachylepis maculilabris (Gray, 1845). Given that the type material for Trachylepis albopunctata, T. angolensis, and T. anchietae has been lost or destroyed, we designate neotypes for the purpose of nomenclatural stability. The description of the new species and the revision and revalidation of previously described Angolan species contribute to a better understanding of the taxonomy and biogeography of the genus, as well as to the general biogeo- graphic patterns and evolution of the Angolan fauna.

The Trachylepis (Squamata: Scincidae) of Angola: An Integrative Taxonomic Review with the Description of Seven New Species - Ceríaco, Luis M.P.; Marques, Mariana P.; Parrinha, Diogo; Tiutenko, Arthur; Weinell, Jeffrey L.; Butler, Brett O.; Bauer, Aaron M. (Bulletin of the American Museum of Natural History, 2024)
The genus Trachylepis is currently represented by 21 species in Angola, most of them part of nomenclaturally and taxonomically challenging species complexes. In this study we present an integrative taxonomic revision of the genus in Angola and describe seven new species: Trachylepis attenboroughi, sp. nov., Trachylepis bouri, sp. nov., Trachylepis hilariae, sp. nov., Trachylepis ovahelelo, sp. nov., Trachylepis suzanae, sp. nov., Trachylepis vunongue, sp. nov., and Trachylepis wilsoni, sp. nov. As result of our taxonomic revisions, 25 valid Trachylepis species are now confirmed from Angola. A phylogenetic analysis using a combination of mitochondrial (16S, ND2) and nuclear (RAG1) markers, as well as morphological data, supports the recognition of the new species. In addition, data support the revalidation of Trachylepis albopunctata (Bocage, 1867), Trachylepis notabilis (Peters, 1879), and Trachylepis ansorgii (Boulenger, 1907). We also provide a redefinition of Euprepes anchietae Bocage, 1866, which we synonymize with Trachylepis maculilabris (Gray, 1845). Given that the type material for Trachylepis albopunctata, T. angolensis, and T. anchietae has been lost or destroyed, we designate neotypes for the purpose of nomenclatural stability. The description of the new species and the revision and revalidation of previously described Angolan species contribute to a better understanding of the taxonomy and biogeography of the genus, as well as to the general biogeographic patterns and evolution of the Angolan fauna.
CRIS-Team Scopus Importer:2024-03-08

Unveiling an enigma from the Cerrado: taxonomic revision of two sympatric species of Apostolepis Cope, 1862 (Dipsadidae: Xenodontinae: Elapomorphini) from central Brazil - Entiauspe-Neto, Omar M.; Koch, Claudia; Guedes, Thais B.; Paredero, Rafael C. B.; Tiutenko, Arthur; Loebmann, Daniel (European Journal of Taxonomy, 2022)
Apostolepis albicollaris and A. cerradoensis are two Elapomorphini snake species, described within a short timespan, from the Cerrado of central Brazil. In their brief descriptions, these two species were diagnosed from congeners largely based on highly variable external morphological characters. Interestingly enough, A. cerradoensis has remained known based on a single specimen since its description. Here, we present a reanalysis of both type specimens, as well as a careful examination of a large series of specimens formerly assigned to these species, based on the comparison of internal and external morphology. We conclude that both species are synonymous, providing evidence for the recognition of A. cerradoensis as a junior synonym of A. albicollaris. Furthermore, an account of its updated diagnosis, morphological variation, geographic distribution, hemipenial morphology, phylogenetic relationships and an osteological description are also provided. We also discuss its conservation status, suggesting that the species is under threat and qualifies to be listed as Vulnerable (VU ab(iii)), considering its rarity, small geographic range, and persistent environmental threats.
CRIS-Team Scopus Importer:2022-06-03
Keywords: Caenophidia; conservation; Dry Diagonal; Squamata; synonymization